DAMPAK LIBERALISASI WTO TERHADAP KETAHANAN PANGAN BERAS DAN GULA - Adrian D. Lubis; Reni K. Arianti (Buletin Ilmiah Litbang Perdagangan, 2011)
This paper goals are to study impact of trade liberalization and Indonesia capability to maintain national food security for rice and sugar. This study that uses multiregression analysis with dummy variabels and GTAP found that import of rice and sugar increase due are to lack of capability to fulfill national consumption. Therefore, Indonesia must increase its rice and sugar productivity to fulfill national food security in liberalization regime.